2014
DOI: 10.1371/journal.pone.0095131
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of French Bacillus anthracis Strains Based on 31-Loci Multi Locus VNTR Analysis: Epidemiology, Marker Evaluation, and Update of the Internet Genotype Database

Abstract: Background Bacillus anthracis is known to have low genetic variability. In spite of this lack of diversity, multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA) and single nucleotide polymorphisms (SNPs) including the canonical SNPs assay (canSNP) have proved to be highly effective to differentiate strains. Five different MLVA schemes based on a collection of 31 VNTR loci (MLVA8, MLVA15, MLVA20, MLVA25 and MLVA31) with increased resolving power have been described.ResultsMLVA31 was applied to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…The MLVA-10 scheme developed in the present study was shown to be an appropriate tool to detect epidemic strains of B. cenocepacia, due to the high stability of MLVA profiles, the satisfactory discriminatory power, and the portability of the method, allowing the establishment of a Web-based database (http://mlva.u-psud.fr) (14). We suggest the use of MLVA as a first-line typing method for B. cenocepacia and further analyses of the representative MLVA profiles by means of MLST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLVA-10 scheme developed in the present study was shown to be an appropriate tool to detect epidemic strains of B. cenocepacia, due to the high stability of MLVA profiles, the satisfactory discriminatory power, and the portability of the method, allowing the establishment of a Web-based database (http://mlva.u-psud.fr) (14). We suggest the use of MLVA as a first-line typing method for B. cenocepacia and further analyses of the representative MLVA profiles by means of MLST.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MLVA is a cost-effective typing method that provides portable results, with the MLVA codes consisting of an unequivocal string of numbers that can easily be exchanged between laboratories and made accessible via internet databases (12). MLVA codes can also be deduced from wholegenome sequence data (14). An MLVA scheme has been developed to type Burkholderia pseudomallei (15,16).…”
mentioning
confidence: 99%
“…MLVA genotyping was applied in order to establish whether several genotypes circulated in the epidemic zone. We initially used loci vrrA, Bams03, Bams05, Bams22, Bams44, and vntr23 derived from the MLVA7 scheme proposed by Thierry et al [27]. This set of loci allowed to genotype all isolates during one day with a high degree of reliability and proved to be very useful in conducting an epidemiological investigation, when it is required to minimize the time spent on analysis, down to hours.…”
Section: Resultsmentioning
confidence: 99%
“…Later it turned out that the same MLVA profile was found in all strains isolated in the summer of 2016 on the Yamal, regardless of the isolation place (Lake Pisyoto area, Novoportovskaya tundra, Evayakha River area) and of the institution by which the samples were analyzed (S1 table) even when using 25 loci. Querying the Bacillus anthracis v4_0 MLVA database at http://microbesgenotyping.i2bc.paris-saclay.fr [27] indicates that the Yamal strains belong to the B-clade [29]. All genotypes present in the MLVA database differed at four loci or more among the 25 loci.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation